PENGARUH PENDAPATAN ASLI DAERAH(PAD), DANA ALOKASI UMUM (DAU), DAN DANA ALOKASI KHUSUS (DAK) TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL PADA PEMERINTAHAN KABUPATEN/KOTA DI SUMATERA UTARA PADA TAHUN 2013-2015 - Benny Franco Sitompul (Jurnal Akrab Juara, 2019)
The research objective is to test and analyze the effect of regional original income, general allocation funds and special allocation funds on the allocation of capital expenditure budget to district / city governments in North Sumatra in 2013-2015. This study uses a quantitative research approach. The type of research used is descriptive research. The nature of this study is a causal relationship. The population used in this study is the district / city government in North Sumatra in 2013-2015 which amounted to 34 cities. A sample of 26 cities in North Sumatra with total sample of 34 cities. The research method used is pooled data which is a combination of periodic data with cross data. Regional original revenue, general allocation funds and special allocation funds have a positive and significant effect on the capital expenditure budget in district/city governments in North Sumatra in 2013-2015.